Effects of Nigella sativa on disease activity, T lymphocytes and inflammatory cytokine profiles in pediatric systemic lupus erythematosus: A randomized controlled trial - Barlianto, Wisnu; Wulandari, Desy; Sari, Tita L.; Rachmaningrum, Rafika R.; Asasain, Rayi I. (Narra Sains Indonesia, 2024)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with diverse manifestations, requiring long-term treatment that can have side effects, particularly in pediatric patients. Nigella sativa (NS) has shown potential for improving SLE symptoms due to its anti-inflammatory and immunomodulatory effects. The aim of this study was to investigate the immunomodulatory effect of N. sativa oil (NSO) on disease activity, T lymphocyte activity and inflammatory cytokine profiles in pediatric SLE patients. A randomized, double-blinded, placebo-controlled clinical trial was conducted at Saiful Anwar Hospital in Malang, Indonesia, from January 2022 to January 2023. Pediatric patients with SLE were randomly assigned to receive either one gram of NSO or a placebo containing starch in capsule form as adjunct therapy alongside their SLE primary treatment. Blood samples were collected before treatment and after eight weeks of daily capsules. Disease activity was assessed using the SLE Disease Activity Index 2000 (SLEDAI-2K); flow cytometry was used to identify T helper lymphocytes, and serum cytokine levels were measured using ELISA. The statistical analysis tests were performed to compare the outcomes between groups at baseline or after the treatment, and within-group comparisons before and after the study period, as appropriate. A total of 32 patients were included in the study. A significant decrease in the SLEDAI-2K score was observed at post-treatment in both the NSO and placebo groups (p<0.001 and p=0.025, respectively). The percentage of T helper 17 (Th17) cells was significantly reduced in both the NSO and placebo groups post-treatment compared to pre-treatment (p=0.026 and p=0.034, respectively). Conversely, the post-treatment percentage of regulatory T (Treg) cells increased significantly in both groups. A significant reduction in interleukin (IL)-2 levels was observed in the NSO and placebo groups at post-treatment compared to pre-treatment (p=0.006 and p=0.046, respectively). Additionally, there were increases in IL-4 and IL-6 serum levels in both groups at post-treatment compared to pre-treatment (p<0.05). This study highlights that although disease activity was not significantly different between NSO and placebo groups, NSO could affect the inflammatory cytokine profiles in pediatric SLE patients.